Respuesta :

Answer:

2y

Step-by-step explanation:

2x-3=2y

2x-2y=3

Answer:

x = 3, y = 1.5

Step-by-step explanation:

Given the 2 equations

x + 2y = 6 → (1)

2x - 3 = 2y → (2)

In (2) subtract 2y from both sides and add 3 to both sides

2x - 2y = 3 → (3)

Adding (1) and (3) term by term will eliminate the y- term

3x = 9 ( divide both sides by 3 )

x = 3

Substitute x = 3 into either of the 2 equations and solve for y

Substituting into (1)

3 + 2y = 6 ( subtract 3 from both sides )

2y = 3 ( divide both sides by 2 )

y = 1.5